Kesulitan Siswa Sekolah Dasar dalam Memahami Konsep Pecahan - Meitesya Putri; Salmaini Safitri Syam; Chandra Chandra (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to examine in-depth and comprehensively the various obstacles faced by elementary school students in understanding the concept of fractions. Fractions represent one of the key components in basic mathematics education and often pose a significant challenge for many students. Through a structured literature review and in-depth analysis of empirical data, this research seeks to clearly describe the various difficulties students encounter when learning and understanding fractions. Additionally, this study investigates the underlying factors contributing to these difficulties and offers a number of creative and effective instructional strategy recommendations to help students overcome these barriers. The findings indicate that the primary challenges hindering students' understanding include several critical aspects: weak comprehension of basic fraction concepts, difficulty in representing fractions both visually and symbolically, struggles with performing arithmetic operations involving fractions, and challenges in relating fraction concepts to real-life situations. A thorough understanding of these challenges is expected to serve as a crucial foundation for improving the quality of mathematics instruction at the elementary school level.